2023
DOI: 10.1186/s40001-023-01281-6
|View full text |Cite
|
Sign up to set email alerts
|

The cause and effect of gut microbiota in development of inflammatory disorders of the breast

Yibo Gu,
Muye Hou,
Jinyu Chu
et al.

Abstract: Background Inflammatory disorders of the breast (IDB) damages the interests of women and children and hinders the progress of global health seriously. Several studies had offered clues between gut microbiota (GM) and inflammatory disorders of the breast (IDB). The gut–mammary gland axis also implied a possible contribution of the GM to IDB. However, the causality between them is still elusive. Methods The data of two-sample Mendelian randomization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…2022). While Ruminiclostridium6 is not well-studied, some MR analyses associate it with the risk of moderate to severe asthma, scoliosis, and breast inflammatory disease (Gu et al, 2023;Lai et al, 2023;Li et al, 2023). Over the past few decades, research has increasingly revealed the "gut microbiota-pancreatic axis", highlighting the mutual influence between gut bacteria and the pancreas (Schepis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2022). While Ruminiclostridium6 is not well-studied, some MR analyses associate it with the risk of moderate to severe asthma, scoliosis, and breast inflammatory disease (Gu et al, 2023;Lai et al, 2023;Li et al, 2023). Over the past few decades, research has increasingly revealed the "gut microbiota-pancreatic axis", highlighting the mutual influence between gut bacteria and the pancreas (Schepis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%